Green synthesis of bispidinols as fluorescent/radio imaging precursors in cancer therapy: insight into structural and biological elucidation - Bandapalli Palakshi Reddy; Rajesh Kancherla; Sundaramoorthy Sarveswari; Arshad Khan; Imadul Islam; Yasinalli Tamboli; Vijayaparthasarathi Vijayakumar (Green Chemistry Letters and Reviews)
The bispidinone and bispidinol derivatives were synthesized using green synthetic methodologies and isolated in high yield without column chromatographic purification. The chemical structures of newly synthesized compounds were elucidated using spectroscopic techniques like IR, 1D & 2D NMR, and HRMS. The pivotal step, the reduction of the carbonyl group to alcohol, was developed by utilizing silica chloride and sodium borohydride. Their unique chemical structures offer versatility for functionalization, allowing for the introduction of specific moieties tailored to desired applications. Furthermore, the investigation into their anti-bacterial, anti-fungal, anti-oxidant, and cytotoxicity properties underscores their therapeutic potential. The compound 5n emerged as the best antimicrobial agent with low cytotoxicity. Subsequently, the green synthesis of bispidinones and bispidinols are valuable precursors to developing novel biomedical tools with diverse applications in imaging and cancer therapy, leveraging the unique properties of bispidine-derived compounds.